Assessment of heart transplant recipients survival based on ultrasound diagnostic methods and immunological screening of antibodies to leukocyte donor antigens - L. K. Tkhatl; T. V. Stavenchuk; A. A. Khalafyan; E. Kosmacheva; Irina Pashkova (Российский кардиологический журнал)
Aim. To create a mathematical model for predicting an assessment of the risk of antibody-mediated rejection (AMR) and analyze the survival of recipients with antibodies to leukocyte donor antigens.Material and methods. A single-center study was conducted on the basis ofS.V.OchapovskyRegionalClinicalHospital № 1. During the 7 years 181 heart transplant recipients were observed. Based on the AMR crisis and detected antibodies to leukocyte donor antigens (HLA), 5 groups were identified: group 1 (n=10) — donor-specific antibodies (DSA) and AMR crisis, group 2 (n=7) — patients without DSA and AMR crisis, group 3 (n=17) — patients with antibodies to HLA, without AMR crisis, group 4 (n=11) — with AMR crisis, without identified antibodies to HLA, group 5 (n=87) — patients, not having antibodies to HLA and signs of both AMR and cell-mediated rejection (according to endomyocardial biopsy). The recipients underwent immunological tests, 2D-speckletracking echocardiography (2D-STE) and transthoracic echocardiography (TTEchoCG). Statistical methods were used to assess the results.Results. Predictors of the severe form of AMR in TTEchoCG are: left ventricle enddiastolic diameter, interventricular septum thickness, ejection fraction, right ventricle volume. Predictors were determined using the 2D-STE method: global longitudinal peak strain, sensitivity (SE) — 86,2%, specificity (SP) — 90,4%; radial strain, SE — 75,8%, SP — 84,5%; circular strain, SE — 78,6%, SP — 84,4%. When taking into account the indicators of the global longitudinal peak strain of the left ventricle and the longitudinal peak strain of the right ventricle, SE increases to 91,9%, SP — 94,6%, with p<0,001. The survival rate of patients with identified post-transplant (de novo) donor-specific antibodies of the late period is 40%, without identified donor-specific antibodies — 68%. Dedicated predictors are used for mathematical prediction of AMR risk.Conclusion. The relationship between immunological changes and data of TTEchoCG, deformation parameters and mechanics of a heart transplant was revealed. The presence of de novo DSA decline the survival, increases the risk of AMR, and contributes to the development of coronary artery disease. The proposed AMR risk prediction model will improve the long-term results of heart transplantation.